SRD5A3-CDG: Emerging Phenotypic Features of an Ultrarare CDG Subtype - Kamarus Jaman, Nazreen; Rehsi, Preeya; Henderson, Robert H.; Löbel, Ulrike; Mankad, Kshitij; Grunewald, Stephanie (Frontiers in Genetics, 2021)
Background: SRD5A3-CDG is a rare N-glycosylation defect due to steroid 5 alpha reductase type 3 deficiency. Key feature is an early severe visual impairment with variable ocular anomalies often leading to diagnosis. Additional symptoms are still ill defined. In this case study we discuss eleven genetically confirmed cases and report on emerging features involving other systems in addition to the eye phenotype. Methods: Eleven SRD5A3-CDG patients of five sets of sibships were included in the study. Data on nine of eleven patients are yet unpublished. Patients’ results on biochemical and genetic investigations, and on in depth phenotyping are presented. Results: Key diagnostic features of SRD5A3-CDG are ophthalmological abnormalities with early onset retinal dystrophy and optic nerve hypoplasia. SRD5A3-CDG is also characterized by variable neurological symptoms including intellectual disability, ataxia, and hypotonia. Furthermore, ichthyosiform skin lesions, joint laxity and scoliosis have been observed in our cohort. We also report additional findings including dystonia, anxiety disorder, gastrointestinal symptoms, and MRI findings of small basal ganglia and mal-rotated hippocampus. Whereas previous publications described dysmorphic features as a common finding in SRD5A3, this could not be confirmed in our patient cohort. Conclusion: The detailed description of the phenotype of this large cohort of patients with SRD5A3-CDG highlights, that the key clinical diagnostic features of SRD5A3-CDG are an early onset of ophthalmological problems in patients with a multisystem disorder with variable symptoms evolving over time. This should aid earlier diagnosis and confirms the need for long-time follow up of patients.